Perceval Implantation and Ascending Replacement: Which Should Be Performed First? - Santarpino, Giuseppe; Specchia, Luigi; Mastroroberto, Pasquale; Gregorini, Renato (AORTA, 2021)
The use of sutureless prostheses has expanded due to their ability to reduce surgical times, thus favoring their implantation in high-risk patients. It is not uncommon that these patients have an ascending aortic aneurysm requiring treatment with a vascular prosthesis; therefore, using a sutureless aortic valve may be associated. To date, however, little is known about the time sequence of this intervention, that is, if sutureless implantation should precede or follow that of the vascular prosthesis.
Keywords: aortic aneurysm; aortic valve and root; heart valve surgery